Pertanggungjawaban Retribusi Parkir di Dinas Perhubungan Kota Palembang Tahun 2018 - Abdul Rauf; Sisca Nopralia (Jurnal Ilmu Administrasi dan Studi Kebijakan (JIASK), 2019)
The research entitled “The Parking Fees in Transportation Agencies In Palembang”, aimed to determine the accountabilty of acceptance parking fees by Transportation Agencies in Palembang through qualitative aspect of receiving report, developed from approach of public accountability. The method in this research uses qualitative method in the form of descriptive. The data retrieval techniques are about observation, interview, and documentation. This research uses public accountability theory which is explained by J. B Ghartey is about the collection of parking fees. The actor who is involved in collecting of parking fees and the value which is got from collecting the parking fees.